Perceptions and predictors of respectful maternity care in Malawi: A quantitative cross-sectional analysis. (September 2022) - Hughes, Carolyn Smith; Kamanga, Martha; Jenny, Alisa; Zieman, Brady; Warren, Charlotte; Walker, Dilys; Kazembe, Abigail
Highlights: Overt abuse and a lack of basic amenities was uncommon (<5%). A lack of consent and engagement in decision-making was frequent (>40%). More than half of women were not allowed to have a companion during delivery. Predictors of experience of care include timing of ANC, mother-infant complications. Findings may inform improvements in quality, including communication and consent. Abstract: Objective: Access to high-quality, respectful care is a basic human right. A lack of respectful care during childbirth is associated with poor outcomes and can negatively influence care-seeking and maternal mental health. We aimed to describe how women perceive their experience of maternity care in Malawi. Methods: We implemented a cross-sectional survey of women ( n = 660) who delivered in 25 birth facilities in four districts in Malawi in March 2020 using a validated 30-item, 90-point person-centered maternity care (PCMC) scale. We used descriptive statistics to examine women's experience of care and analyzed bivariable and multivariable mixed-effects models to evaluate predictors of PCMC. Statistical models accounted for clustering of women at the facility level and included maternal age, marital status, education, parity, mother or infant complications, timing of antenatal care (ANC), provider cadre and gender, facility type and sector, and district. Results: Mean PCMC score was 57.5 (range 21-84), with the lowest score (12.4 of 27 points) in communication and autonomy. Women reported: being prohibited from having a birth companion during labor (49.4%) or delivery (60.3%); providers did not introduce themselves (81.1%); providers did not ask consent before procedures/examinations (42.4%); women felt they could not ask questions (40.9%); and were not involved in care decisions (61.5%). Few women reported being frequently abused physically (2%) or verbally (3.5%); almost all had water/electricity available (>95%). In bivariate analyses, statistically significant positive associations were found between PCMC score and early ANC, male accompaniment to the facility, male provider, and a lack of complications; all associations remained at least potentially statistically significant in multivariable modeling. Conclusions: Physical and verbal abuse and a lack of basic amenities were rare, while a lack of communication with patients and social support were common. Maternal characteristics (like timing of ANC and maternal or newborn complications) were predictors of RMC, while facility/system factors, like facility type and sector, were not. Continued efforts to improve respectful care will require strengthening provider communication skills and encouraging patient and companion involvement in care.